Validity of the Scientific Creativity Project Based Learning (SiPjBL) Model in physics learning to increase the scientific creativity of physics education undergraduate students in basic physics courses 1 - Sumo, Maimon; Jatmiko, Budi; Supardi, Zainul Arifin Imam (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to describe the validity of the SiPjBL model reviewed from the aspects of model development needs and knowledge updates. The method used is development. The data collection technique is carried out by model validation and the research instrument is a model validation sheet containing statements referring to aspects of development needs and knowledge updates. Data analysis is carried out quantitatively by calculating the score on each component of each aspect of the model. The results of the study obtained an average score of 3.92 with a very valid category and the percentage of feasibility of the SiPjBL model reached 97%. Thus, the SiPjBL model is feasible to be implemented in the learning process in higher education.